Atomistic insight into the hydration and proton conducting mechanisms of the cobalt doped Ruddlesden-Popper structure Sr3Fe2O7-δ. (26th May 2020) - Chen, Meina; Xuan, Yan; Zhang, Feng; He, Lei; Wang, Xue; Pan, Huaqing; Ren, Junfeng; Lin, Zijing
Abstract: Sr3 Fe2 O7-δ (SFO) with two-layer Ruddlesden-Popper (R–P) structure has recently been proved to be a promising material for the single phase cathode in proton conducting solid oxide fuel cells (P–SOFCs). To investigate the hydration reactions and proton conducting mechanisms of SFO and cobalt doped SFO (SFCO), both bulk and surface properties were calculated. We conclude that R–P structures have advantages in P–SOFCs. The unique Sr–O–M layer can facilitate the hydration process. Although in Sr–O–F and Sr–O–N layers, it is difficult for the formation and migration of oxygen vacancies, protons are most stable. Furthermore, cobalt doping can not only improve the electronic conductivity but also enhance surface properties of SFCO. The easily exposed Co–Fe–O surface can also facilitate the hydration reactions on the surface. Our work could give an informative insight into the relationships among the doped elements, the R–P structures, the hydration process and the proton conducting properties. Graphical abstract: Image 1 Highlights: Calculation on hydration and proton transport mechanism of R–P structure SFO and SFCO. The unique Sr–O–M layer can facilitate the hydration process. In rock-salt layers, protons are stable, formation and migration of O 2− are difficult. Cobalt doping can improve electronic conductivity and surface properties. Easily exposed Co–Fe–O surface can facilitate the hydration reactions on the surface.